Democracy, Accountability, and Evaluation - Jan-Eric Furubo (Journal of MultiDisciplinary Evaluation)
Background: The focus of the article concerns the final step in the accountability chain in democratic societies, the one between the people and their elected representatives. The importance of this relationship has meant that questions regarding accountability and independent scrutiny have been important in the democratic discussions for more than 2300 years. Based on a discussion of this relationship, the article asks the question of what role evaluation can have in strengthening this relationship.